Infodemiology of Anthrax in Indonesia: Insights from Google Trends (2014–2024) - Fadhillah, Risti Sifa'; Utami, Putri; Sarkowi, Widya Khairunnisa; Iryawati, Dinda (UNUSA Press, 2025)
Background: Anthrax remains a persistent zoonotic disease in Indonesia, with recurrent outbreaks reported in endemic provinces such as Yogyakarta, Gorontalo, Central Java, and East Nusa Tenggara. Outbreak control is further challenged by the circulation of misinformation, which shapes community perceptions and undermines prevention efforts. Digital epidemiology offers opportunities to complement conventional surveillance by capturing public information-seeking behavior, yet its application in anthrax research in Indonesia remains limited. Methods: This study analyzed temporal and spatial dynamics of public interest in anthrax using Google Trends data from January 2014 to December 2024. Two search terms, antraks (Indonesian) and anthrax (English), were examined to assess monthly patterns, regional distribution, and related search queries. Descriptive analyses were performed to identify peaks of interest, geographic differences, and themes of related and rising queries. Results: Overall search activity was low and stable throughout the 11 years, with distinct peaks corresponding to outbreaks, most notably in July 2023 during the Yogyakarta outbreak. Regional analysis revealed Yogyakarta and Gorontalo as the dominant provinces of search activity. Linguistic patterns showed that antraks was more widely used in western Indonesia, while anthrax was relatively more frequent in eastern provinces. Related queries reflected demand for basic knowledge of symptoms, transmission, and prevention, while rising queries aligned with outbreak-related events. Conclusion: Online search patterns mirror epidemiological risk, cultural context, and digital access. Infodemiology provides timely insights that may enhance outbreak preparedness and risk communication. Integrating digital surveillance with conventional monitoring can support more effective and locally relevant health education strategies for anthrax control in Indonesia.